Andrew Murray Jr as entrepreneur - Murray, Montagu (Stellenbosch Theological Journal, 2022)
This article explores a novel perspective on Andrew Murray Jr, namely his entrepreneurial spirit and characteristics. Instead of building on the view that he was a mystic who gained his energy to contribute to the practical challenges of everyday life in the spiritual realm, the article explores to which extent Murray's role in the modernisation of Christian mission and education in South Africa can be attributed to an entrepreneurial character. The article investigates how his family history, personality, and exposure to various influences during his early life, shaped him to approach his ministry entrepreneurially. These influences include elements from various strands in the protestant tradition, including Lutheranism, Calvinism, pietism, Methodism, and the inner-worldly asceticism of English puritanism, as famously described by Max Weber. The analysis concludes that Andrew Jr approached his calling of preaching the gospel and growing the church to convert unreached souls to the love of Christ in an entrepreneurial manner.